2010
DOI: 10.1093/rpd/ncq252
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on accurate measurements of thoron with airflow-through scintillation cell method

Abstract: For accurate measurements of (220)Rn concentration with airflow-through scintillation cell method, a theoretical study was performed for discussing the influences of sampling flow rate, volumes of sampling tube and scintillation cell on the measurements. It is found that a high flow rate and a large inner volume of scintillation cell as well as a small inner volume of sampling tube are not only preferable for measuring low levels of (220)Rn, but also helpful for enhancing the measurement accuracy. In calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Other factors taken into account were Lucas cell calibration data (Kritidis, 1982) and inflow decay of 220 Rn (e.g. (Tang et al, 2010)). The reference integrated concentration was calculated by multiplying the average 220 Rn concentration by the exposure time (with air-flow breaks subtracted).…”
Section: Methodsmentioning
confidence: 99%
“…Other factors taken into account were Lucas cell calibration data (Kritidis, 1982) and inflow decay of 220 Rn (e.g. (Tang et al, 2010)). The reference integrated concentration was calculated by multiplying the average 220 Rn concentration by the exposure time (with air-flow breaks subtracted).…”
Section: Methodsmentioning
confidence: 99%
“…Its inner lateral wall is coated with ZnS(Ag) scintillator to detect alpha particles. To reduce the influence of thoron decay during measurement, which has been systematically discussed in our previous study [27], a relatively higher airflow rate of 2.7 L min -1 was used for this scintillation cell. The detection chamber of the PIPS device is a cylindrical volume with a diameter of 50.0 mm and a height of 11.3 mm (V = 22.2 mL).…”
Section: Laboratory Validation and Testmentioning
confidence: 99%
“…Among these detectors, scintillation cells have gained widespread popularity owing to their high sensitivity and simplicity of use [14][15][16][17]. The thoron measurement methods employing scintillation cells can be classified into three types: (1) the grab-sample method initially developed by Hutter [15] and subsequently improved by others [16][17][18][19][20]; (2) the delayed coincidence method proposed by Giffin et al [21] and further developed by others [22][23][24][25]; and (3) the airflow-through method, which is commonly used for radon measurement but less studied for thoron measurement [26][27][28]. Although the grab-sample method and the delayed coincidence method offer an advantage over the airflow-through method as they can distinguish between thoron and radon, this disadvantage of the airflow-through method could be overcome as further elaborated in the Discussion section.…”
Section: Introductionmentioning
confidence: 99%
“…Using different volumes of an improved cylinder scintillation cell to measure Rn-222 activity concentration by grab sample, the efficiencies for the cell volumes between 0.49 l and 1.7 l ranged between 0.038 Bq m −3 min −1 and 0.123 Bq m −3 min −1 , with an overall decrease of 15% observed when increasing the pressure from 827 hPa to 1013 hPa [11]. In the measurement experiments of Rn-220 activity concentration by airflow-through scintillation cell method, Tang et al found that a high flow rate and a large inner volume of scintillation cell, as well as a small inner volume of sampling tube, were not only preferable for measuring low levels of Rn-220 but also helpful for enhancing the measurement accuracy [12].…”
Section: Introductionmentioning
confidence: 99%